Correlation between airborne manganese concentration at the workstations in the iron foundry and manganese concentration in workers' blood - Seyedtaghi Mirmohammadi; Yosef Moghaddasi; Jamshid Yazdani; Razyeh Yousefinejad; Yahya Esfandyari; Mohsen Gorgani; Manijeh Habibpour (Nofer Institute of Occupational Medicine, 2017)
Background: Manganese (Mn) used as raw material for melting process in the ferrous foundry is considered as hazardous neurotoxic substance because it accumulates in the central nervous system and may cause neurological disorders. The furnace-men and melting department workers are potentially exposed to manganese particles or fume in the workplace. The objective of the research has been to investigate the sources and levels of manganese exposure in the foundry by correlation of blood-manganese (B-Mn) and air-manganese (air-Mn) measurement. Material and Methods: Air-Mn and Mn of blood serum were measured involving workers who worked in a big-sized foundry during 1 year. The standard method of the Occupational Safety and Health Administration (OSHA) ID-121 was used for air and blood assessment and atomic absorption spectroscopy (AAS) was carried out for air and blood sample analysis. Results: The air sampling results have revealed that there is a high exposure to manganese (4.5 mg/m3) in the workplace as compared to the National Institute for Occupational Safety and Health's (NIOSH) time weighted average (the reference time-weighted average (TWA) = 1 mg/m3). The average blood serum Mn concentration was 2.745 μg/l for subjects working for shorter than 3 months and 274.85 μg/l for subjects working 3-12 months. Conclusions: Against the research hypothesis there was no correlation between the air-Mn concentration and the B-Mn (serum) level of manganese in the serum of the exposed subjects. It may be due to short time of air sampling of manganese airborne particles, and a real-time monitoring of airborne manganese particles is suggested for any future study. Med Pr 2017;68(4):449-458